High maternal milk intake in the postnatal life reduces the incidence of breast cancer during adulthood in rats. (10th January 2019) - Santiano, F. E.; Zyla, L. E.; Verde-Arboccó, F. Campo; Sasso, C. V.; Bruna, F. A.; Pistone-Creydt, V.; López-Fontana, C. M.; Carón, R. W.
Abstract: Environmental factors during perinatal life can lead to changes in the mammary gland, making it susceptible to cancer in adulthood. Breastfeeding has a special importance since it takes place at a critical period of growth and development of the newborn. We aimed to analyze if an appropriate lactation protects the offspring against mammary carcinogenesis during adult life and explore the mechanisms involved in the protective effect. One-day-old Sprague-Dawley female rats were randomly distributed in litters of three (L3), eight (L8) or 12 (L12) pups per dam, to induce a differential consumption of breast milk. At 55 days of age, the animals were treated with a single dose of dimethylbenzanthracene to study tumor latency, incidence and progression. Histological, immunohistochemical and Western blot studies were performed. We observed lower incidence and higher latency in L3 compared to the other groups. The mitotic index and expression of proliferating cell nuclear antigen (PCNA) was significantly augmented in tumors of L12 rats compared to L3 and L8, while the apoptotic index was augmented in tumors of L3 v . L12. Cleaved caspase 8 was significantly higher in tumors from L3 compared to L12. Tumors developed in L3 have a greater number of apoptotic bodies and a greater expression of caspase 8. These results demonstrate that the animals that maintained a higher intake of maternal milk (L3) presented lower incidence and greater tumor latency. Lower consumption of breast milk (L12) would increase tumor mitosis and the expression of PCNA, explaining the higher tumor incidence observed in this group.